Signaler credibility, signal susceptibility, and relative reliance on signals: How stakeholders change their evaluative processes after violation of expectations and rehabilitative efforts - GOMULYA, David (Institutional Knowledge at Singapore Management University, 2017)
Prior studies have shown that a firm’s violation of expectations might lead to less favorable evaluations of that firm by stakeholders. However, the literature has been silent on whether and how the process by which stakeholders evaluate a firm could change subsequent to the violation. Drawing from signaling and screening theory, we examine how evaluative processes might change in the context of financial restatements. We find that investors appear to shift their relative reliance on particular signals in determining a firm’s stock price following an earnings restatement. These changes are at least partly reversed following the replacement of an incumbent CEO. We further find that these evaluative changes vary depending on the severity of the violation.